(untitled) (Balneo and PRM Research Journal, 2022)
ABSTRACT: Sarcopenia or degeneration of skeletal muscle tissue with aging, is responsible for functional decline and loss of independence in older adults. The purpose of this article is to review the current definitions of sarcopenia, its potential causes, clinical consequences and the potential for prophylactic and curative intervention. Sarcopenia is recognized as a major clinical problem for the elderly, and the research in this area is growing exponentially. One of the most important recent developments has been convergence in the operational definition of sarcopenia that combines muscle mass, strength and muscle function. In 2010, the European Working Group on Sarcopenia in Oder People (EWGSOP) published a definition of sarcopenia aimed at promoting progress in the identification and care of the elderly. In early 2018 (EWGSOP2) he met again to update the original definition to reflect the scientific and clinical evidence that has been built over the past decade. The cause of sarcopenia is considered to be multifactorial: hormonal changes, neurological decline, sedentary / immobilization for a long period, chronic diseases, obesity, all these factors contribute to the onset of sarcopenia. Prophylactic or curative interventions are essentially aimed at nutrition and exercise. Although pharmaceutical agents are developed that target several biological pathways, proper nutrition and specific physical exercises remain the gold standard for therapy. Through this review, we want to draw attention to the need to implement complex analyzes of the elderly patient, regardless of the acute problem with which he presents himself at the consultation. These analyses should contain tests, measurements, questionnaires that identify in time a possible musculoskeletal degeneration. The results did not show any significant difference between the perception of sarcopenia, the way of approaching it and the prophylactic or therapeutic treatment. We focused on this pathology because sarcopenia is relatively newly observed, defined, it is not fully investigated and a clinical skill has not been formed for the evaluation of the elderly patient. Keywords: Skeletal muscle, elderly, sarcopenia, degeneration, exercises